ГАЗЕТА МАҚАЛАЛАРЫНА ТЕМА ҚОЙЫЎДЫҢ ТЕОРИЯЛЫҚ МƏСЕЛЕЛЕРИ - Қурбаниязов, Д. (SCIENCE and SOCIETY, 2020)
The article reviews the study of newspaper headlines. There are given the definitions of headings and functional features of headings. It is emphasized the necessity of the research in the Karakalpak linguistics of newspaper headlines on the semantic-structural and stylistic aspects.